Risk factors for thrombotic events in Philadelphia chromosome-negative myeloproliferative neoplasms: a retrospective analysis of 336 cases - Zhang, Lingxiu; Wang, Xiufeng; Yang, Man; Zi, Youmei; Zhang, Yuan; Guo, Yan; Lv, Guoqing; Wu, Sun; Huang, Yan (Frontiers in Oncology, 2025)
Thrombotic events are one of the main factors affecting the survival of patients with Philadelphia chromosome-negative (Ph-) myeloproliferative neoplasms (MPNs). Therefore, a comprehensive understanding of the early relevant high-risk factors makes sense for early prevention and reducing mortality in these patients. In this study, we conducted a retrospective analysis of 336 patients with Ph- MPN and summarized the clinical characteristics, incidence of thrombotic events and influencing factors. Thrombotic events occurred in 27.7% (93/336) of patients. Among the thrombotic events, arterial thrombosis occurred in 86 cases (92.5%), the most common thrombotic event was cerebral infarction (69/93, 74.2%). Univariate analysis and logistic regression identified that diagnosis of Polycythemia Vera (PV)/Essential Thrombocythemia (ET), thrombotic events before diagnosis and D-dimer≥1mg/L were the independent risk factors for thrombotic events at initial diagnosis in MPN patients (P<0.05). Receiver operating characteristic (ROC) curve analysis revealed that the integrated predictive efficacy of the triple-variable combination was markedly superior to that of any single parameter alone, yielding a sensitivity of 72.04% (95% CI: 61.8%-80.9%), a specificity of 74.49% (95% CI: 68.5%-79.8%), and an area under the curve (AUC) of 0.771 (95% CI: 0.723 - 0.815). Additionally, univariate analysis further identified smoking history, elevated hemoglobin (Hb≥136g/L), hematocrit (HCT≥0.42), D-dimer-to-fibrinogen ratio (DFR≥0.243) and JAK2V617F mutation as potential risk factors for thrombosis (P<0.05), necessitating validation in future studies. These findings facilitate the early identification of Ph-MPN patients at heightened risk for thrombotic events, enabling the implementation of targeted prophylactic strategies to mitigate thrombotic risk.